2016
DOI: 10.2320/matertrans.m2015448
|View full text |Cite
|
Sign up to set email alerts
|

Binary Systems of Kaolinite and Hematite: Preparation, Characterization and Adsorption Characteristics for Fluoride

Abstract: In soils and sediments kaolinite (Kao) and hematite (Hem) are often cemented together as binary systems, which have a signi cant in uence on the mobility of nutrients and pollutants in natural environments. In this study, the binary systems of kaolinite-hematite complex (KHC) and kaolinite-hematite mixture (KHM) were prepared, and the surface properties and uoride adsorption of the samples were investigated. Compared to KHM, the XRD peaks for both kaolinite and hematite in KHC were lower. The crystallinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The BC used in all these experiments was of same batch with particle size distribution as shown in Figure 2 and the MCRW was collected once with physical properties as shown in Table 3. The capacity of adsorbents to adsorb a solute from a solution is expressed in grams of solute adsorbed per gram of adsorbent (Wei et al, 2016). For this study, BC fluoride removal capacity was estimated by considering a fixed amount of mg of fluoride adsorbed.…”
Section: Comparison Of Adjusting Mcrw Ph and Treatment Of Bc With Acid Before Use On Defluoridationmentioning
confidence: 99%
“…The BC used in all these experiments was of same batch with particle size distribution as shown in Figure 2 and the MCRW was collected once with physical properties as shown in Table 3. The capacity of adsorbents to adsorb a solute from a solution is expressed in grams of solute adsorbed per gram of adsorbent (Wei et al, 2016). For this study, BC fluoride removal capacity was estimated by considering a fixed amount of mg of fluoride adsorbed.…”
Section: Comparison Of Adjusting Mcrw Ph and Treatment Of Bc With Acid Before Use On Defluoridationmentioning
confidence: 99%
“…Fluoride adsorption has been extensively studied with respect to specific soil components kaolinite and bentonite (Anderson, Zelazny, & Bertsch, 1991;Bar-Yosef, Afik, & Rosenberg, 1988;Kau, Smith, & Binning, 1998), aluminium and iron hydroxide minerals (Hiemstra & Van Riemsdijk, 2000;Meeussen, Scheidegger, Hiemstra, VanRiemsdijk, & Borkovec, 1996;Nordin, Sullivan, Phillips, & Casey, 1999) and a binary clay-mineral (kaolinitehaematite) substrate system (Wei et al, 2016). These studies have demonstrated that F − adsorption by individual soil components generally results in increased solution pH, attributable to anion exchange between F − and surface OH − groups.…”
Section: Introductionmentioning
confidence: 99%